Integration of Cryo-EM Model Building Software in Scipion - Martínez, M; Jiménez-Moreno, A; Maluenda, D; Ramírez-Aportela, E; Melero, R; Cuervo, A; Conesa, P; Del Caño, L; Fonseca, Y C; Sánchez-García, R; Strelak, D; Conesa, J J; et al. (Journal of chemical information and modeling, 2020)
Advances in cryo-electron microscopy (cryo-EM) have made it possible to obtain structures of large biological macromolecules at near-atomic resolution. This "resolution revolution" has encouraged the use and development of modeling tools able to produce high-quality atomic models from cryo-EM density maps. Unfortunately, many practical problems appear when combining different packages in the same processing workflow, which make difficult the use of these tools by non-experts and, therefore, reduce their utility. We present here a major extension of the image processing framework Scipion that provides inter-package integration in the model building area and full tracking of the complete workflow, from image processing to structure validation.
Keywords: Image Processing, Computer-Assisted; průběh práce; Software; elektronová kryomikroskopie; počítačové zpracování obrazu; software; Workflow; Cryoelectron Microscopy